Respuestas

2013-12-26T12:15:58+01:00
(x-3)/7+(x+1)/2=3/14
(2(x-3)+7(x+1))/14=3/14
2x-6+7x+7=3
9x+1=3
9x=2
x=2/9
¡La mejor respuesta!
  • Usuario de Brainly
2013-12-26T12:23:48+01:00
 \frac{x-3}{7} + \frac{x+1}{2} = \frac{3}{14}

Primero pasamos todo a común denominador:

 \frac{2*(x-3)}{14} + \frac{7*(x+1)}{14} = \frac{3}{14}

\frac{2x-6}{14} + \frac{7x+7}{14} = \frac{3}{14}

\frac{2x-6+7x+7}{14}= \frac{3}{14}

2x-6+7x+7= \frac{3*14}{14}

2x-6+7x+7= 3

9x+1=3

9x=3-1

9x=2

x =  \frac{2}{9} = 0,22


Solución:
x = 2/9     Forma fraccionaria
x = 0,22   Forma decimal